Siti Walidah : Pelopor Emansipasi dan Pendidikan Perempuan Dalam Muhammadiyah - Syahla Sri Dhiya Ulhaq; Alvira Fitriani; Najwa Qholivia Putri; Dzulfikar Rafi; Hanafiah Hanafiah; Laila Nur Az Zahro; Astika Nurul Hidayah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Siti Walidah, or Nyai Ahmad Dahlan, became an important figure in fighting for women's education and emancipation through the establishment of the 'Aisyiyah organization. Siti Walidah's struggle was based on the patriarchal cultural conditions in the past that limited women's access to education and social roles. Siti Walidah, through her progressive thinking, tried to change this paradigm by establishing a women's organization under Muhammadiyah that emphasized the importance of education, empowerment, and gender equality. This study aims to analyze the thoughts and contributions of Siti Walidah in shaping the role of women, especially through education and empowerment, and to trace its impacts that are still felt today. The research method used is qualitative with a historical approach, through literature studies of primary documents such as the archives of Muhammadiyah and 'Aisyiyah, as well as the biography of Siti Walidah. The data were analyzed descriptively-interpretively to understand the social, cultural, and religious contexts that underlie her struggle. The results of the study show that through the 'Aisyiyah organization, Siti Walidah promoted women's education, opposed discriminatory practices such as forced marriage, and developed various social and economic empowerment programs. Another significant contribution was the establishment of educational institutions, such as TK 'Aisyiyah Bustanul Athfal and Aisyiyah University.